2015
DOI: 10.1002/jgt.21855
|View full text |Cite
|
Sign up to set email alerts
|

Independent Domination in Cubic Graphs

Abstract: International audienceA set S of vertices in a graph G is an independent dominating set of G if S is an independent set and every vertex not in S is adjacent to a vertex in S. The independent domination number of G, denoted by inline image, is the minimum cardinality of an independent dominating set. In this article, we show that if inline image is a connected cubic graph of order n that does not have a subgraph isomorphic to K2, 3, then inline image. As a consequence of our main result, we deduce Reed's impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 7 publications
0
44
0
1
Order By: Relevance
“…still open, and as a partial result, Dorbec et al [6] showed that the conjecture holds if in addition G does not have a subgraph isomorphic to K 2,3 . For other conjectures and partial results regarding the independent domination number of subclasses of cubic graphs, see [2,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…still open, and as a partial result, Dorbec et al [6] showed that the conjecture holds if in addition G does not have a subgraph isomorphic to K 2,3 . For other conjectures and partial results regarding the independent domination number of subclasses of cubic graphs, see [2,7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Using Theorem 1.3 and an idea in [20], we prove Theorem 1.4 in Section 3. In Section 4, we prove a statement slightly stronger than Theorem 1.5, where the proof adopts the approach of [6].…”
Section: Introductionmentioning
confidence: 99%
“…We remark that several papers, see for example [1,2,3,11,19], in which upper bounds are obtained on the independent domination number of cubic graphs present more general results on subcubic graphs.…”
Section: Motivation and Known Resultsmentioning
confidence: 82%
“…Dorbec, Henning, Montassier, and Southey [3] proved Conjecture 1 in the case when there is no subgraph isomorphic to K 2,3 . In general, however, Conjecture 1 remains unresolved.…”
Section: Motivation and Known Resultsmentioning
confidence: 99%
See 1 more Smart Citation